Annual report of the Inter-American Institute of agricultural Sciencies. Fiscal year 1945 -46 - Instituto Interamericano de Ciencias Agrícolas (IICA) (IICA, 2020)
Although this is the Fourth annual report, the IICA was established officially only on december 1, 19444. Previous to the dato plants had been introduced and same breeding work begun, but the period between december and the end of the fiscal year 1945-46 was largely devoted to the tremendous task of preparing to do research and teaching.